Cancer statistics for African Americans, 2016: Progress and opportunities in reducing racial disparities. (22nd February 2016) - DeSantis, Carol E.; Siegel, Rebecca L.; Sauer, Ann Goding; Miller, Kimberly D.; Fedewa, Stacey A.; Alcaraz, Kassandra I.; Jemal, Ahmedin
Abstract : In this article, the American Cancer Society provides the estimated number of new cancer cases and deaths for blacks in the United States and the most recent data on cancer incidence, mortality, survival, screening, and risk factors for cancer. Incidence data are from the National Cancer Institute, the Centers for Disease Control and Prevention, and the North American Association of Central Cancer Registries, and mortality data are from the National Center for Health Statistics. Approximately 189, 910 new cases of cancer and 69, 410 cancer deaths will occur among blacks in 2016. Although blacks continue to have higher cancer death rates than whites, the disparity has narrowed for all cancers combined in men and women and for lung and prostate cancers in men. In contrast, the racial gap in death rates has widened for breast cancer in women and remained level for colorectal cancer in men. The reduction in overall cancer death rates since the early 1990s translates to the avoidance of more than 300, 000 deaths among blacks. In men, incidence rates from 2003 to 2012 decreased for all cancers combined (by 2.0% per year) as well as for the top 3 cancer sites (prostate, lung, and colorectal). In women, overall rates during the corresponding time period remained unchanged, reflecting increasing trends in breast cancer combined with decreasing trends in lung and colorectal cancer rates. Five‐year relative survival is lower for blacks than whites for most cancers at each stage of diagnosis. The extent to which these disparities reflect unequal access to health care versus other factors remains an active area of research. Progress in reducing cancer death rates could be accelerated by ensuring equitable access to prevention, early detection, and high‐quality treatment.CA Cancer J Clin 2016;66:290‐308. © 2016 American Cancer Society